2003
DOI: 10.1074/jbc.m300970200
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Gene Expression and the Altered Accumulation of Scleral Collagen during the Development of High Myopia

Abstract: The development of high myopia is associated with reduced scleral collagen accumulation, scleral thinning, and loss of scleral tissue, in both humans and animal models. Reduced collagen fibril diameter is also observed in the sclera of eyes with high myopia. The present study investigated aspects of scleral collagen synthesis and degradation, in a mammalian model of high myopia, to elucidate the factors underlying scleral changes. General synthesis and degradation of scleral collagen was investigated in monocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 35 publications
(50 reference statements)
6
123
2
Order By: Relevance
“…eyes (Gentle et al 2003). The study also found that posterior scleral collagen degradation was significantly increased in eyes developing myopia.…”
Section: Introductionsupporting
confidence: 58%
“…eyes (Gentle et al 2003). The study also found that posterior scleral collagen degradation was significantly increased in eyes developing myopia.…”
Section: Introductionsupporting
confidence: 58%
“…It is predicted that alterations in scleral matrix properties have a function in the pathobiology of myopia (21). For example, collagen and proteoglycan expression is reduced in the sclera of a myopic animal model (45), and collagen fibril ultrastructure is altered with an increased number of smaller diameter collagen fibrils (23). This loss of matrix was shown to result from reduced collagen and proteoglycan production as well as increased collagen degradation by matrix metalloproteinases (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…For example, collagen and proteoglycan expression is reduced in the sclera of a myopic animal model (45), and collagen fibril ultrastructure is altered with an increased number of smaller diameter collagen fibrils (23). This loss of matrix was shown to result from reduced collagen and proteoglycan production as well as increased collagen degradation by matrix metalloproteinases (44,45). Interestingly, only type I collagen (not type III or type V) has exhibited reduced mRNA expression levels in studies of myopic sclera (45).…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, reduced collagen accumulation in the sclera is observed in highly myopic eyes. 23 Importantly, another collagen prolyl hydroxylase-encoded gene, named LEPREL1, has been reported to cause autosomal-recessive high myopia with early-onset cataracts. 13,24 It is also worth noting that several clinical syndromes, such as Stickler syndrome and Marfan syndrome, in which myopia is a prominent characteristic, are caused by defects in collagen.…”
Section: Discussionmentioning
confidence: 99%